The enhancement of heat transfer of wood (Neobalanocarpus Heimii, Shorea Sp, Instia Palembanica Miq) of bio-composite materi als for green building in Malaysia - Amalina Alias; Mazlan Mohamed; Hamid Yusoff; Mohd Hazim Mohamad Amini; M.S. Abdul Aziz; Zairi Ismael Rizman (2015)
In this study, heat transfer investigation is done in or der to improve the cooling effect for green building without damaging the environment. This proposal is provoked by the desire to reduce the temperature for the green building and to sustain the environment and natural resources. The building industry is also a large consumer of non-renewable materials and this trend has increasing dramatically over the past century. To this end, we have been addressing sustainability concerns related to building construction materials through many research approach applied to building elements where we can collectively influence design, mate rials, construction, energy consumption and disposal. Bio- composites can best be used in the building industry today and what fundamental advancements are needed to facilitate more widespread application of these clean, energy-efficient and resource-rich construction materials. The use of heat insulation in the building envelope in hot and humid climate is investigated through computer simulation. Simulation of heat transfer in the aspect of reducing the temperature phenomenon inside the green building using FLUENT-GAMBIT. In this project work the simulation of heat transfer and the temperature curve in the traditional wood house and green building model is computed out using gambit and fluent software. The use of thermal insulation in the building envelope in hot and humid climate is investigated through computer simulation. Comparison of temperature profiles of the material in the traditional wood house and green building model using constant temperature heat source and linearly varying temperature of the heat source for unsteady state is done. Also the time for temperature to become steady is compared. The problem will be solved by using the software package FLUENT – GAMBIT. The parameters under analysis focused on changing the influence of exterior walls in the energy consumption for cooling the building.